Gestação em portadora de arterite de Takayasu Pregnancy follow-up and outcome in a patient with Takayasu's arteritis - Alexandre Jorge Gomes de Lucena; Antonio Carlos Carvalho; Jose Augusto M. Souza; Antonio Fernandes Moron; Sue Y. Sun; Daniel Born (Arquivos Brasileiros de Cardiologia, 2008)
No presente relato, que descreve a gestação de paciente portadora de arterite de Takayasu, serão avaliadas a interação dessa afecção com a gravidez e as intercorrências materno-fetais, do parto e do recém-nascido. We describe here the pregnancy follow-up and outcome in a patient with Takayasu's arteritis, with a detailed account of the complications during gestation and delivery and the impact of the disease on the newborn's health.